Intracellular Signaling by Diffusion: Can Waves of Hydrogen Peroxide Transmit Intracellular Information in Plant Cells? - Vestergaard, Christian L.; Flyvbjerg, Henrik; Møller, Ian M. (Frontiers in Plant Science, 2012)
Amplitude- and frequency-modulated waves of Ca2+ ions transmit information inside cells. Reactive Oxygen Species, specifically hydrogen peroxide, have been proposed a similar role in plant cells. We consider the feasibility of such an intracellular communication system in view of the physical and biochemical conditions in plant cells. As model system, we use a H2O2 signal originating at the plasma membrane and spreading through the cytosol. We consider two maximally simple types of signals, isolated pulses and harmonic oscillations. First we consider the basic limits on such signals as regards signal origin, frequency, amplitude, and distance. Then we establish the impact of ROS-removing enzymes on the ability of H2O2 to transmit signals. Finally, we consider to what extent cytoplasmic streaming distorts signals. This modelling allows us to predict the conditions under which diffusion-mediated signalling is possible. We show that purely diffusive transmission of intracellular information by H2O2 over a distance of 1 µm (typical distance between organelles, which may function as relay stations) is possible at frequencies well above 1 Hz, which is the highest frequency observed experimentally. This allows both frequency and amplitude modulation of the signal. Signalling over a distance of 10 µm (typical distance between the plasma membrane and the nucleus) may be possible, but requires high signal amplitudes or, equivalently, a very low detection threshold. Furthermore, at this longer distance a high level of enzymatic degradation is required make signalling at frequencies above 0.1 Hz possible. In either case, cytoplasmic streaming does not seriously disturb signals. We conclude that although purely diffusion-mediated signalling without relaying stations is theoretically possible, it is unlikely to work in practice, since it requires a much faster enzymatic degradation and a much lower cellular background concentration of H2O2 than observed experimentally.